Kemampuan membaca pemahaman ditinjau dari penguasaan kosakata dan minat baca pada peserta didik kelas v sd - Shinta Maharani; St. Y. Slamet; Sukarno Sukarno (Universitas Sebelas Maret, 2024)
This purpose of this study is to demonstrate how grade V student’s reading comprehension ability (Y) and vocabulary mastery (X1) and reading interest (X2) relate to one another. The study employed a correlational study survey methodology. Students in grade V in public elementary schools in the Laweyan subdistrict during the 2023/2024 academic year made up the study’s population. A basic random sample strategy was employed in the sampling process. Methods for gathering data that involve questionnaires and tests. Tests were used on vocabulary mastery variables and reading comprehension ability. In order to read interest variables, questionnaires were employed. Both simple and multiple correlation analysis were employed as data analysis technique in this study. The result of this study are vocabulary mastery with reading comprehension ability, namely the correlation coefficient r count (0,99) > r table (0,202) with t count significance (67,81) > t table (1,66); the capacity to read comprehension is significantly correlated with, namely the correlation coefficient r count (0,993) > r table (0,202) with t count significance (83,83) > t table (1,66); the capacity to read comprehension is significantly correlated with vocabulary mastery and reading interest together with reading comprehension ability, namely R count (0,993) > R table (0,202), F count significance (3480,92) > F table (3,1) with a real level α = 0,05 and df 93.